Association of tryptophan hydroxylase-2 polymorphisms with oppositional defiant disorder in a Chinese Han population. Issue 1 (December 2016) - Wang, Chang-Hong; Liu, Cong; Cong, En-Zhao; Xu, Gai-Ling; Lv, Ting-Ting; Zhang, Ying-Li; Ning, Qiu-Fen; Wang, Ji-Kang; Nie, Hui-Yao; Li, Yan
Abstract Background Oppositional defiant disorder (ODD) is a behavioral disorder of school-age population. It is well known that 5-HT dysfunction is correlated with impulsivity, which is one of the common characteristics of ODD. The enzyme tryptophan hydroxylase-2 (TPH-2) synthesizes 5-HT in serotonergic neurons of the midbrain raphe. The purposes of this study were to investigate the potential association ofTPH -2 polymorphisms with susceptibility to ODD in a Han Chinese school population. Methods Four polymorphisms (rs4570625, rs11178997, rs1386494 and rs7305115) of the TPH-2 gene were analyzed by using polymerase chain reaction and DNA microarray hybridization in a case–control study of 276 Han Chinese individuals (124 ODD and 152 controls). Results In single marker analyses, there was a significant difference in the genotype (χ 2 = 4.163, P = 0.041) and allele frequency (χ 2 = 3.930, P = 0.047) of rs1386494 between ODD and control groups. Haplotype analyses revealed higher frequencies of haplotypes TA (rs4570625-rs11178997), TAG (rs4570625-rs11178997-rs1386494), TAA (rs4570625-rs11178997-rs7305115) and TAGA (rs4570625-rs11178997-rs1386494-rs7305115), but lower frequencies of haplotypes GA (rs4570625-rs11178997) and GAG (rs4570625-rs11178997-rs1386494) in ODD compared to control groups. Conclusions These findings suggest the role of theseTPH -2 gene variants in susceptibility to ODD. Some haplotypes might be the risk factors for Chinese Han children with ODD, while others might be preventable factors.